STRATEGIC ELEMENT IN HEALTH, OPERATIONAL AND FINANCIAL PERFORMANCE ASSESSMENT: EXAMPLE OF SELCUK UNIVERSITY MEDICAL FACULTY HOSPITAL - Gokbel, Hakkı; Gules, Hasan Kursat; Isiklar, Zeynep Ergen; Sener, Tugba (European Scientific Journal, ESJ, 2015)
Today, transferring resources to the health sector, distribution of transferred resources between health care services, use of resources and quality of provided services are very important in countries. When it became clear that the growing importance of strategic management and development of institutions are connected to provide improvements not only in a sub-unit but also in all sub-unit and in an integrated manner, researches carried out in hospitals reached holistic and administrative size. For a holistic assessment managers focused on the measurement of hospital performance. In this study, we made the operational and financial data analysis of the Hospital of Selcuk University Faculty of Medicine that was established in 2001 and started it’s activities in 2009. In this context, firstly some basic financial ratios were calculated by ratio analysis method based on the hospital’s balance sheet. In the study second, medical statistics which described as operational data were analyzed. In addition some assessment and recommendations were made by comparing basic analysis results to overall Turkey. In this way, the hospital’s current financial and operational performances have comparatively been evaluated.